2013
DOI: 10.1186/1477-7517-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Between harm reduction, loss and wellness: on the occupational hazards of work

Abstract: Those working in the fields of harm reduction, healthcare, and human services must cope with a range of stresses, including post traumatic stress and vicarious trauma. Pain and loss are just a part of the job. So is dealing with premature death as a result of HIV, hypertension, and even overdose. Faced with a range of challenges, some workers in the field even turn to self-medication. For some, it is about pleasure; for others it is about alleviating suffering. In recent years, several leaders in the AIDS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Symptomology can be divided into four broad categories: (a) avoidant behaviors, such as escalated absenteeism from work, withdrawal from family members, social isolation from friends, and/or avoidance of sexual intimacy with partner(s); (b) arousal symptoms, displayed in hyper arousal for the safety of self and loved ones, increase in stress-induced medical conditions and illnesses, general fearfulness, and/or heightened suspicion of others; (c) changes in cognitive schemas, evidenced by engagement in dysfunctional coping skills, decrease in clinical service provision and general work ethic, intensified pessimistic worldview, apathy or negative change in spiritual beliefs; and (d) intrusive imagery through aversive daydreams, mental images, or nightmares (Aparicio et al, 2013;Barrington & Shakespeare-Finch, 2013;Branson et al, 2014;Ilesanm & Eboiyehi, 2012;Mairean & Turliuc, 2012;Mishori, Mujawar, & Ravi, 2014;Possick et al, 2015;Sansbury, Graves, & Scott, 2015;Vrklevski& Franklin, 2008;Wies& Coy, 2013).Research indicates that intrusive imagery is the most commonly endorsed symptom of vicarious trauma (Branson, 2011;Bride et al, 2004). Additional professional symptoms are increased cynicism and/or misplaced anger toward clients, decrease in quality service provision due to avoidance of client disclosures of trauma, poor ethical decision making, and ultimately, practitioners leaving the field altogether due to the rigors of the work (Iqbal, 2015;Pryce et al, 2007;Shepard, 2013).…”
Section: What Is Vicarious Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomology can be divided into four broad categories: (a) avoidant behaviors, such as escalated absenteeism from work, withdrawal from family members, social isolation from friends, and/or avoidance of sexual intimacy with partner(s); (b) arousal symptoms, displayed in hyper arousal for the safety of self and loved ones, increase in stress-induced medical conditions and illnesses, general fearfulness, and/or heightened suspicion of others; (c) changes in cognitive schemas, evidenced by engagement in dysfunctional coping skills, decrease in clinical service provision and general work ethic, intensified pessimistic worldview, apathy or negative change in spiritual beliefs; and (d) intrusive imagery through aversive daydreams, mental images, or nightmares (Aparicio et al, 2013;Barrington & Shakespeare-Finch, 2013;Branson et al, 2014;Ilesanm & Eboiyehi, 2012;Mairean & Turliuc, 2012;Mishori, Mujawar, & Ravi, 2014;Possick et al, 2015;Sansbury, Graves, & Scott, 2015;Vrklevski& Franklin, 2008;Wies& Coy, 2013).Research indicates that intrusive imagery is the most commonly endorsed symptom of vicarious trauma (Branson, 2011;Bride et al, 2004). Additional professional symptoms are increased cynicism and/or misplaced anger toward clients, decrease in quality service provision due to avoidance of client disclosures of trauma, poor ethical decision making, and ultimately, practitioners leaving the field altogether due to the rigors of the work (Iqbal, 2015;Pryce et al, 2007;Shepard, 2013).…”
Section: What Is Vicarious Traumamentioning
confidence: 99%
“…Secondary traumatic stress occurs when professionals are psychologically overwhelmed by their responsibility to provide aid, comfort, and assistance in highly traumatic, frightening, or devastating situations (Figley, 1995). The term is most appropriate for health care professionals, police officers, firefighters, first responders, emergency/crisis medical workers, hospice care professionals, and other specialists who encounter human-based suffering on a regular basis, but do not engage in an empathic relationship (Branson, in press;Shepard, 2013). Symptomology of secondary traumatic stress often presents quickly and is a direct result of a specific encounter.…”
Section: Secondary Traumatic Stress and Other Closely Related Termsmentioning
confidence: 99%
“…Previous research found that, among home visitors, the FAN training fostered reflective capacity and prevented burnout (MacKinnon, 2019) as well as increased mindfulness and sense of self-efficacy (Spielberger, Burkhardt, Winje, & Gouvea, 2017;Spielberger, Burkhardt, Winje, Gouvea, & Barisik, 2016). Despite the potential for reflective practice to have positive benefits for a range of professionals working in child welfare fields, few published studies have examined the potential benefits of participating in the FAN approach among this population (Butler, Carello, & Maguin, 2017;Fansher, Zedaker, & Brady, 2019;Shepard, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, extant research highlights the importance of identifying malleable ways to decrease vicarious trauma among child welfare professionals to prevent burnout (e.g., Branson, 2019;Shepard, 2013). As it is unlikely that the traumatic nature of these professionals' work will change, the current evaluation sought to examine whether the FAN approach to reflective practice can mitigate the relationship between vicarious trauma and burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that working in overdose response settings can be stressful and traumatizing, with lasting social, emotional and mental health effects for individuals [11,[18][19][20][21][22]. Individuals working in overdose response face grief due to the signi cant loss of lives during the overdose epidemic [11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%